Social soil science as a new direction in the science of soils - Pozniak, S.Р. (AgroChemistry and Soil Science, 2018)
The article contains the author's reflections on the formation and substantiation of many aspects in soil science, concerning its connections with social sciences. Arguments about the exceptional importance of soil resources in the modern world and the importance of scientific research in soil science, which can become an important instrument of solving social problems, are found. It is shown that soil resources, being the basis of agricultural development, are the "long-term" capital through which different nations exist and develop. In order to maintain the population normal living conditions and to its improving, it is important to use this global resource wisely. The attitude of people to the soil is recognized as fundamental for nation’s sustainable development and, moreover, the life expectancy of a civilization may depend on the people attitude to soils. In order to maintain collective well-being of people, a long-term interest of the society in soil protection needs to be reoriented - this should become a priority task for our civilization. The current state of soils can be a characteristic of the development of society as well as a criterion for assessing the activity of government and social stability in the country.